Strategi Komunikasi Pemasaran Dinas Pariwisata dan Kebudayaan Kabupaten Pangandaran melalui Media Sosial Instagram @Pangandaran.Tourism - Faizal Rafsanzani; Dewi Kurniasih (Politeknik Pariwisata NHI Bandung, 2022)
Many businesses incorporate social media into their marketing and communications plans. Companies use social media in an effort to attract more customers. The Department of Tourism and Culture (Disparbud) of Pangandaran Regency, is a government agency authorized to manage tourism and culture in the district. The purpose of this study was to describe the social media marketing communication strategy of Instagram Disparbud Pangandaran Regency by combining a descriptive approach with a qualitative approach. Based on the findings of this study, Disparbud Pangandaran Regency carried out a marketing communication strategy consisting of five stages, namely marketing objectives, marketing audiences, message and media design, promotion mix, and evaluation. Through these five stages, it can increase the interest of visits for the marketing communication strategy that has been implemented. However, the increase in tourist interest occurs situationally.